Models for assessing the quality of service: characterization and analysis (Revista Científica Compendium, 2018)
Defining service quality and determining how to evaluate it has caused significant disagreements among authors. In this article, supported by a literature review on some of the most representative assessing models in the scientific literature; they are characterized and analyzed considering their prospects, dimensionality, application and scope. It is found that the customer perception is the most often used in these assessments perspective, highlighting the use of multidimensional models based on external indicators, where tangibility, customer service, reliability, safety, responsiveness and results are the dimensions of evaluation the most used. The Model SERVQUAL despite of being highly questioned and published over 25 years ago, it is still considered an important reference, being quoted, analyzed and applied in many recent research studies, at different types of services.
Keywords: quality of service; assessing model; analysis; state of the art; SERVQUAL